Evaluation and utilization of preassembled frozen commercial fast real‐time qPCR master mixes for detection of cytomegalovirus and BK virus. Issue 1 (17th July 2015) - Glover, William A.; Atienza, Ederlyn E.; Nesbitt, Shannon; Kim, Woo J.; Castor, Jared; Cook, Linda; Jerome, Keith R.
Abstract : Quantitative DNA detection of cytomegalovirus (CMV) and BK virus (BKV) is critical in the management of transplant patients. Quantitative laboratory‐developed procedures for CMV and BKV have been described in which much of the processing is automated, resulting in rapid, reproducible, and high‐throughput testing of transplant patients. To increase the efficiency of such assays, the performance and stability of four commercial preassembled frozen fast qPCR master mixes (Roche FastStart Universal Probe Master Mix with Rox, Bio‐Rad SsoFast Probes Supermix with Rox, Life Technologies TaqMan FastAdvanced Master Mix, and Life Technologies Fast Universal PCR Master Mix), in combination with in‐house designed primers and probes, was evaluated using controls and standards from standard CMV and BK assays. A subsequent parallel evaluation using patient samples was performed comparing the performance of freshly prepared assay mixes versus aliquoted frozen master mixes made with two of the fast qPCR mixes (Life Technologies TaqMan FastAdvanced Master Mix, and Bio‐Rad SsoFast Probes Supermix with Rox), chosen based on their performance and compatibility with existing PCR cycling conditions. The data demonstrate that the frozen master mixes retain excellent performance over a period of at least 10 weeks. During the parallel testing using clinical specimens, no difference in quantitative results was observed between the preassembled frozen master mixes and freshly prepared master mixes. Preassembled fast real‐time qPCR frozen master mixes perform well and represent an additional strategy laboratories can implement to reduce assay preparation times, and to minimize technical errors and effort necessary to perform clinical PCR. J. Med. Virol. 88:115–119, 2016 . © 2015 Wiley Periodicals, Inc.